Biochemical responses and oxidative stress in Francisella tularensis infection: a European brown hare model - Bandouchova, Hana; Pohanka, Miroslav; Vlckova, Kristina; Damková, Veronika; Pecková, Lucie; Sedláčková, Jana; Treml, Frantisek; Vitula, František; Pikula, Jiří (Acta veterinaria Scandinavica, 2011)
BACKGROUND: The aim of the present study was to investigate biochemical and oxidative stress responses to experimental F. tularensis infection in European brown hares, an important source of human tularemia infections. METHODS: For these purposes we compared the development of an array of biochemical parameters measured in blood plasma using standard procedures of dry chemistry as well as electrochemical devices following a subcutaneous infection with a wild Francisella tularensis subsp. holarctica strain (a single dose of 2.6 × 10⁹ CFU pro toto). RESULTS: Subcutaneous inoculation of a single dose with 2.6 × 10⁹ colony forming units of a wild F. tularensis strain pro toto resulted in the death of two out of five hares. Plasma chemistry profiles were examined on days 2 to 35 post-infection. When compared to controls, the total protein, urea, lactate dehydrogenase, aspartate aminotransferase and alanine aminotransferase were increased, while albumin, glucose and amylase were decreased. Both uric and ascorbic acids and glutathione dropped on day 2 and then increased significantly on days 6 to 12 and 6 to 14 post-inoculation, respectively. There was a two-fold increase in lipid peroxidation on days 4 to 8 post-inoculation. CONCLUSIONS: Contrary to all expectations, the present study demonstrates that the European brown hare shows relatively low susceptibility to tularemia. Therefore, the circumstances of tularemia in hares under natural conditions should be further studied.
Keywords: tularemie; látky reagující s kyselinou thiobarbiturovou; Oxidative Stress; mužské pohlaví; oxidační stres; Tularemia; Male; časové faktory; sérový albumin; zajíci; Francisella tularensis; Animals; Time Factors; Hares; zvířata; Thiobarbituric Acid Reactive Substances; Serum Albumin